Cross-Modal Recruitment of Auditory and Orofacial Areas During Sign Language in a Deaf Subject - Martino, Juan; Velasquez, Carlos; Vázquez-Bourgon, Javier; de Lucas, Enrique Marco; Gomez, Elsa (World neurosurgery, 2017)
Modern sign languages used by deaf people are fully expressive, natural human languages that are perceived visually and produced manually. The literature contains little data concerning human brain organization in conditions of deficient sensory information such as deafness. A deaf-mute patient underwent surgery of a left temporoinsular low-grade glioma. The patient underwent awake surgery with intraoperative electrical stimulation mapping, allowing direct study of the cortical and subcortical organization of sign language. We found a similar distribution of language sites to what has been reported in mapping studies of patients with oral language, including 1) speech perception areas inducing anomias and alexias close to the auditory cortex (at the posterior portion of the superior temporal gyrus and supramarginal gyrus); 2) speech production areas inducing speech arrest (anarthria) at the ventral premotor cortex, close to the lip motor area and away from the hand motor area; and 3) subcortical stimulation–induced semantic paraphasias at the inferior fronto-occipital fasciculus at the temporal isthmus. The intraoperative setup for sign language mapping with intraoperative electrical stimulation in deaf-mute patients is similar to the setup described in patients with oral language. To elucidate the type of language errors, a sign language interpreter in close interaction with the neuropsychologist is necessary. Sign language is perceived visually and produced manually; however, this case revealed a cross-modal recruitment of auditory and orofacial motor areas.